IMPELEMENTASI PENDIDIKAN ISLAM INTEGRATIF SEBAGAI UPAYA PENGAUATAN KARAKTER PESERTA DIDIK DI MADRASAH - Deassy Aresta; Indah Citra Soleha; Ahda Khilwa Sabrina; Muhammad Rizky Ihsan; Ahmad Wildan; Muhammad Fajril Munir; Rabahul Sri Nate (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Madrasahs have a distinctive role in the education system by combining religious teachings with general knowledge in a balanced learning environment. This educational approach is known as integrative Islamic education, which seeks to develop students not only in terms of academic achievement but also in their moral values, religious commitment, and social responsibility. This study discusses the implementation of integrative Islamic education in madrasahs and examines the principles that support its practice in the learning process. A qualitative method with a library research approach was employed by reviewing books, scholarly articles, and other relevant academic sources related to the topic. The collected data were examined, organized, and interpreted descriptively to gain a deeper understanding of the concept. The study found that the implementation of integrative Islamic education is reflected in the integration of religious and general subjects, the development of a school culture based on Islamic values, and teachers' efforts to incorporate ethical and spiritual values into classroom activities. These practices encourage students to strengthen their academic competence while nurturing positive character, responsibility, and concern for others. Despite several practical challenges, including limited educational resources and differences in teachers' instructional approaches, integrative Islamic education remains a relevant educational model for preparing students to face contemporary challenges without neglecting Islamic values.